Poor agreement of objectively measured and self-reported physical activity in juvenile dermatomyositis and juvenile systemic lupus erythematosus. Issue 6 (June 2016) - Pinto, Ana; Roschel, Hamilton; Benatti, Fabiana; Sá Pinto, Ana; Sallum, Adriana; Silva, Clóvis; Gualano, Bruno
Abstract To examine the agreement and association between objectively measured and indirectly assessed physical activity levels in patients with juvenile dermatomyositis (JDM) and juvenile systemic lupus erythematosus (JSLE) patients. The sample consisted of 19 JDM patients (age 8 to 22 years) and 20 JSLE patients (age 9 to 18 years). Physical activity level was objectively measured using Actigraph® accelerometers and indirectly assessed by the short-form International Physical Activity Questionnaire (IPAQ). Spearman's correlation coefficients were calculated to test possible associations between physical activity levels across the two instruments. The Bland–Altman technique was used to calculate bias and limits of agreement. Correlations between objectively measured and indirectly assessed physical activity levels in JDM and JSLE were weak, varying fromR = 0.03 toR = 0.33 (allp > 0.05). Total physical activity was correlated between accelerometer and IPAQ in JSLE (R = 0.51, p = 0.021). Bland–Altman analyses suggested that IPAQ tended to highly underestimate sedentary time and light physical activity in JDM (mean bias 105.7 and 199.8 min, respectively) and JSLE (mean bias 36.4 and 127.8 min, respectively). Mean biases of moderate-to-vigorous physical activity were also highly variable, ranging from −42.9 to 54.9 min and −59.4 to 89.8 min for JDM and JSLE, respectively. IPAQ was shown to not be valid to assess physical activity levels in patients with JDM and JSLE when compared against accelerometry. While the validation of reliable self-reported instruments that measure physical activity in pediatric rheumatic patients remains necessary, the use of validated tools that objectively measure physical activity is recommended in both clinical and research settings.